1999
DOI: 10.1364/ol.24.000605
|View full text |Cite
|
Sign up to set email alerts
|

Pupil-plane filtering for improved signal detection in an optical data-storage system incorporating a solid immersion lens

Abstract: A pupil-plane filtering technique is applied to data-signal detection in an optical data-storage system that uses a solid immersion lens (SIL) and a four-layered phase-change recording medium. We have confirmed by numerical calculations and experiment that the technique improves signal contrast and makes the contrast less sensitive to the gap width between the bottom surface of the SIL and the top surface of the recording medium. Light that is incident upon the objective lens that is used with the SIL is linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In contrast, two maximum regions along the x direction show i x Ͼi A . Milster et al 15 used a pupil-plane filtering to block the negative distribution to improve signal contrast.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, two maximum regions along the x direction show i x Ͼi A . Milster et al 15 used a pupil-plane filtering to block the negative distribution to improve signal contrast.…”
Section: Resultsmentioning
confidence: 99%
“…2D irradiance distribution at the exit pupil plane is calculated by summing the squares of the x, y, and z components of the electric field. 11,12) A 4-f (focal length) imaging system introduced in the previous paper 6,7) is used again in order to investigate the effect of the exit pupil plane filtering without disturbing the optical path from the light source to the recording medium. The specific optical filter is located on the image plane of the original pupil.…”
Section: Modulation Of Signal Contrast Corresponding To the Media Ind...mentioning
confidence: 99%
“…Reversed signal levels can be improved by using special filter positioned at exit pupil plane on condition that particular recording media and X-polarized light. 6,7) However, circular polarized light is preferred rather than Xpolarized light considering actual manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to increase the air-gap while keeping the signal contrast and the storage density at an acceptable level. Milster et al [2] showed that the signal contrast can be improved by placing a pupil filter in front of the SIL. Hirota et al [3] filled the air-gap with a liquid lubricant to increase the total internal refraction angel at the lower interface of the SIL.…”
Section: Introductionmentioning
confidence: 99%